Reducing Contact Resistance and Boosting Device Performance of Monolayer MoS2 by In Situ Fe Doping. Issue 18 (3rd April 2022) - Li, Hui; Cheng, Mo; Wang, Peng; Du, Ruofan; Song, Luying; He, Jun; Shi, Jianping
Abstract: 2D semiconductors are emerging as plausible candidates for next‐generation "More‐than‐Moore" nanoelectronics to tackle the scaling challenge of transistors. Wafer‐scale 2D semiconductors, such as MoS2 and WS2, have been successfully synthesized recently; nevertheless, the absence of effective doping technology fundamentally results in energy barriers and high contact resistances at the metal–semiconductor interfaces, and thus restrict their practical applications. Herein, a controllable doping strategy in centimeter‐sized monolayer MoS2 films is developed to address this critical issue and boost the device performance. The ultralow contact resistance and perfect Ohmic contact with metal electrodes are uncovered in monolayer Fe‐doped MoS2, which deliver excellent device performance featured with ultrahigh electron mobility and outstanding on/off current ratio. Impurity scattering is suppressed significantly thanks to the ultralow electron effective mass and appropriate doping site. Particularly, unidirectionally aligned monolayer Fe‐doped MoS2 domains are prepared on 2 in. commercial c ‐plane sapphire, suggesting the feasibility of synthesizing wafer‐scale 2D single‐crystal semiconductors with outstanding device performance. This work presents the potential of high‐performance monolayer transistors and enables further device downscaling and extension of Moore's law. Abstract : A controllable Fe doping strategy is developed in centimeter‐sized monolayer MoS2 films with ultralow contact resistance. Excellent device performance featured with ultrahigh electron mobility and on/off current ratio is achieved, thanks to the ultralow electron effective mass. Unidirectional Fe‐MoS2 domains are prepared on 2 in. commercial c ‐plane sapphire, suggesting the feasibility of synthesizing wafer‐scale single‐crystal semiconductors with outstanding device performance.